Protein Degradation in Normal and Beige (Chediak-Higashi) Mice - Lyons, Robert T. (1978)
The beige mouse, C57BL/6 (bg/bg), is an animal model for the Chediak-Higashi syndrome in man, a disease characterized morphologically by giant lysosomes in most cell types. Half-lives for the turnover of [(14)C]bicarbonate-labeled total soluble liver protein were determined in normal and beige mice. No significant differences were observed between the normal and mutant strain for both rapidly and slowly turning-over classes of proteins. Glucagon treatment during the time-course of protein degradation had similar effects on both normal and mutant strains and led to the conclusion that the rate of turnover of endogenous intracellular protein in the beige mouse liver does not differ from normal. The rates of uptake and degradation of an exogenous protein were determined in normal and beige mice by intravenously injecting (125)I-bovine serum albumin and following, in peripheral blood, the loss with time of phosphotungstic acid-insoluble bovine serum albumin and the parallel appearance of phosphotungstic acid-soluble (degraded) material. No significant differences were observed between beige and normal mice in the uptake by liver lysosomes of (125)I-bovine serum albumin (t(½) = 3.9 and 2.8 h, respectively). However, it was found that lysosomes from livers of beige mice released phosphotungstic acid-soluble radioactivity at a rate significantly slower than normal (t(½) = 6.8 and 3.1 h, respectively). This defect in beige mice could be corrected by chronic administration of carbamyl choline (t(½) = 3.5 h), a cholinergic agonist which raises intracellular cyclic GMP levels. However, no significant differences between normal and beige mice were observed either in the ability of soluble extracts of liver and kidney to bind [(3)H]cyclic GMP in vitro or in the basal levels of cyclic AMP in both tissues. The relevance of these observations to the presumed biochemical defect underlying the Chediak-Higashi syndrome is discussed.